Inhibition of complement C3 and fibrinogen interaction: a potential novel therapeutic target to reduce cardiovascular disease in diabetes. (26th February 2015) - King, Rhodri; Tiede, Christian; Simmons, Katie; Fishwick, Colin; Tomlinson, Darren; Ajjan, Ramzi
Abstract: Background: Enhanced complement C3 incorporation into the fibrin network in diabetes is one mechanism for impaired fibrinolysis and increased thrombosis risk in this condition. Our aim was to develop new strategies to modulate fibrinolysis in diabetes by interfering with fibrin–C3 interaction. Methods: To modulate interaction between fibrinogen and C3 we used a novel technique by screening fibrinogen with a phage display library of 3 billion random, conformational 9AA peptides (termed adhirons). The effect of high affinity fibrinogen binding adhirons, released by the addition of excess C3, on fibrin clot lysis and structure was assessed in turbidimetric assays. Fibrinogen–C3 interactions were further studied by peptide microarray techniques and modelled with the website PepSite2. Findings: Ten high affinity fibrinogen binding adhirons, released by C3, were available for turbidimetric analysis. One adhiron (A6) was found to have a sequence homology with C3 and studied further. In the absence of C3, adhiron A6 failed to modulate fibrin clot lysis time (mean 644 s [SE 13] and 620 [14] without and with adhiron A6, respectively). However, adhiron A6 abolished C3-induced prolongation of clot lysis, reducing mean lysis time from 728 s (SE 25) to 632 (24) (p=0·01). The peptide microarray screening of C3 identified two peptide motifs within the β chain of fibrinogen (residues 424–433, 435–445) that bound to C3. PepSite2 predicted that adhiron A6 binds to similar areas on the β chain of fibrinogen. Interpretation: Using a novel phage display system, we discovered an adhiron that shared sequence homology with C3 and abolished C3-induced prolongation of fibrin clot lysis by interfering with C3–fibrinogen interaction within the β chain. This technique offers a unique method to identify new therapeutic targets for the reduction of diabetes-specific thrombosis risk. Funding: Sir Jules Thorn Charitable Trust.